Audiologists’ attitudes and practice toward referring for psychosocial intervention with cochlear implant patients - Warren, Sarah E.; Barron, Autumn L. (Frontiers in Rehabilitation Sciences, 2024)
Background: Hearing loss is associated with a range of poor psychosocial outcomes. Cochlear implants (CI) are an available treatment option for significant hearing loss and have been linked to improved quality of life in patients. Evidence suggests that audiologists lack the skills to appropriately detect, address, and refer for psychosocial needs among patients with hearing loss. The objective of this study is to examine the attitudes and practice patterns related to psychosocial care among audiologists who work with CI users.A cross-sectional survey was administered to clinical audiologists who work with CI recipients in the United States. The survey evaluated participants' attitudes toward psychosocial services and factors that contribute to their abilities to address the psychosocial needs of their patients. Additionally, participants were surveyed about their practice patterns including the use of psychosocial screeners, clinical protocols regarding psychosocial care, and referral patterns for coordinated psychosocial services. Descriptive statistics were used to summarize survey responses.Results: Sixty-eight audiologists completed the survey. Of these audiologists, a majority (73.6%) held the attitude that most or all CI patients would benefit from psychosocial intervention. Despite clinicians' recognition of psychosocial needs in this population, over 90% of participants reported never screening for psychosocial symptoms. Additionally, a majority of respondents indicated that they seldom refer their patients for psychosocial services, with referrals occurring less than half the time (58%) or never (27%). Additionally, few audiologists reported utilizing protocols or resources for guiding psychosocial practices. Audiologists indicated that the primary factors that influence their psychosocial practices include time available to spend with the patient and their comfort level in counseling.Audiologists working with CI patients recognize the potential benefit of psychosocial intervention in this population. Nevertheless, audiologists encounter barriers in clinical practice which limit their ability to identify and address the psychosocial needs of their patients. Strategies designed to enhance audiologists' capacity to recognize the psychosocial needs of CI users, in addition to improved interprofessional practice on CI teams, implies significant opportunities to improve the provision of patient-centered hearing care.